A case of unstable bradycardia requiring comprehensive management in the emergency department: BRASH syndrome - Sinan Genc; Omer Yusuf Erdurmus; Abdullah Erhan; Ahmet Burak Oguz; Ayca Koca; Muge Gunalp Eneyli; Onur Polat (Emergency Care Journal, 2022)
Bradycardia, renal failure, Atrioventricular (AV) nodal Blocker Drug Use, Shock, and Hyperkalemia (BRASH) syndrome is a clinical condition frequently seen in emergency services but with low diagnostic awareness. In cases of the syndrome, its cause was determined to be the synergistic effect of hyperkalemia due to renal failure and the use of AV nodal blocker drugs. The common features of patients diagnosed with BRASH syndrome are moderately elevated potassium levels and symptomatic bradycardia with various ECG findings (such as junctional bradycardia, atrioventricular block, and sinus bradycardia). Detection of these findings is very important in the diagnosis process. In this case report, we aimed to reveal the important points in the diagnosis of BRASH syndrome, ECG findings, and treatment approach.